2014
DOI: 10.1186/1748-717x-9-135
|View full text |Cite
|
Sign up to set email alerts
|

Repeated stereotactic body radiotherapy for oligometastatic prostate cancer recurrence

Abstract: PurposeTo assess the outcome of prostate cancer (PCa) patients diagnosed with oligometastatic disease at recurrence and treated with stereotactic body radiotherapy (SBRT).MethodsNon-castrate patients with up to 3 synchronous metastases (bone and/or lymph nodes) diagnosed on positron emission tomography - computed tomography, following biochemical recurrence after local curative treatment, were treated with (repeated) SBRT to a dose of 50 Gy in 10 fractions or 30 Gy in 3 fractions. Androgen deprivation therapy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
245
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(266 citation statements)
references
References 31 publications
13
245
2
3
Order By: Relevance
“…In their group (42/124 patients with prostate cancer) they found that irradiation to the single dose of 23-24Gy resulted in better local control of the lesions (2-year LC of 82% in whole group) although no correlation between the dose and LC was observed in prostate cancer group [12]. Very good results were also published by Muacevic et al [13,14,16]. Results obtained in our group are comparable to those reported in literature.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In their group (42/124 patients with prostate cancer) they found that irradiation to the single dose of 23-24Gy resulted in better local control of the lesions (2-year LC of 82% in whole group) although no correlation between the dose and LC was observed in prostate cancer group [12]. Very good results were also published by Muacevic et al [13,14,16]. Results obtained in our group are comparable to those reported in literature.…”
Section: Discussionsupporting
confidence: 81%
“…Also other researchers observed a decrease in PSA concentration during follow-up [11,13,14,17]. PSA concentration at last control was lower in patients with PSA below 20 ng/ml at the time of metastasis detection and based on data of other researchers similar observations can be made [11].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Decaestecker et al performed a study of 50 patients with prostate primaries, with three or fewer metastatic lesions, all treated with SABR [19]. Multiple sites were treated including lymph nodes, liver, and bone (22% of which involved lesions in the axial skeleton).…”
Section: Discussionmentioning
confidence: 99%
“…This is longer than expected in a group with metastases. A prolonged interval before systemic therapy change or initiation is required may reduce side effects associated with systemic therapy initiation or change, which may have an impact on quality of life [18,19].…”
Section: Discussionmentioning
confidence: 99%